2013
DOI: 10.1186/2046-4053-2-51
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric and content analysis of the Cochrane Complementary Medicine Field specialized register of controlled trials

Abstract: BackgroundThe identification of eligible controlled trials for systematic reviews of complementary and alternative medicine (CAM) interventions can be difficult. To increase access to these difficult to locate trials, the Cochrane Collaboration Complementary Medicine Field (CAM Field) has established a specialized register of citations of CAM controlled trials. The objective of this study is to describe the sources and characteristics of citations included in the CAM Field specialized register.MethodsBetween 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Following appraisal of the 17 guidelines, ARG met with JYN and LL to discuss and resolve any uncertainties without unduly modifying legitimate discrepancies. This review does not address all CAM therapies; three therapies were chosen (herbal medicine, acupuncture, chiropractic or osteopathic manipulation) because they were identified as having the largest evidence base, and were therefore considered more likely to be the subject of guidelines [39]. We may not have identified all guidelines that included these three types of CAM therapy because, to establish a feasible scope, we did not search for guidelines on specific clinical topics and then peruse them for CAM-related content, and we did not search all CAM journals or the Guidelines International Network guideline library.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following appraisal of the 17 guidelines, ARG met with JYN and LL to discuss and resolve any uncertainties without unduly modifying legitimate discrepancies. This review does not address all CAM therapies; three therapies were chosen (herbal medicine, acupuncture, chiropractic or osteopathic manipulation) because they were identified as having the largest evidence base, and were therefore considered more likely to be the subject of guidelines [39]. We may not have identified all guidelines that included these three types of CAM therapy because, to establish a feasible scope, we did not search for guidelines on specific clinical topics and then peruse them for CAM-related content, and we did not search all CAM journals or the Guidelines International Network guideline library.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to interventions , guidelines were more likely to have been published on CAM interventions for which evidence has accumulated. We referred to a bibliometric and content analysis of CAM trials in the Cochrane Library by Wieland et al [39] which found that the CAM therapies most commonly evaluated in trials included herbal supplements (non-vitamin, non-mineral dietary supplements or Chinese herbal medicine), acupuncture, and chiropractic or osteopathic manipulation [39]. For this study, guidelines were eligible if they specifically focused on any of these CAM therapies (category 1 – CAM-specific), or were general CAM guidelines that included at least one recommendation (for or against) at least of these CAM therapies (category 2 – CAM-general).…”
Section: Methodsmentioning
confidence: 99%
“…As a simple form of big data analysis, it is useful in revealing historical development [20], quantifying existing trends [24], and predicting the future in a given research domain. Bibliometric methods have been applied to medical related topics [2632] including complementary and alternative medicine [3335]. The results of these findings can be used as context for analyzing broad scale strengths and gaps in the current state of evidence in a field, and for informing a comprehensive strategic plan for further advancing the field.…”
Section: Introductionmentioning
confidence: 99%
“…The Complementary Medicine Field Specialised Register contains trials identified from CENTRAL, Chinese databases, Korean databases, and multiple small databases that have been identified as good sources of complementary medicine trials (Wieland 2013). …”
Section: Methodsmentioning
confidence: 99%